The sac-4 gene of Neisseria gonorrhoeae and co-existing chlamydial infection. Issue 5 (1st October 2000) - Phillips, D J; Patrizio, C; Moyes, A; Young, H
Abstract : Background/objectives: Recently, the sac-4 gene in Neisseria gonorrhoeae was postulated to increase the risk of developing mixed gonococcal and chlamydial infection. The aims of this study were to determine the frequency of the sac-4 gene in a larger sample of isolates of different serovars and to assess the prevalence of sac-4 in gonococcal isolates from patients with and without coexisting chlamydial infection. Methods: Isolates from 259 episodes of gonorrhoea were tested by a PCR assay for the sac-4 gene. The presence of co-existing chlamydial infection was determined from both laboratory and GUM clinical records. Results: The overall prevalence of sac-4 was 57.5% (149/259). The prevalence was not the same in all serovars and ranged from 34.9% in serovar 1B2 to 100% in serovar 1B18. Exact logistic regression analysis indicated significant differences in sac-4 prevalence in isolates of different serovars. The prevalence of sac-4 was 69.5% (41/59) in gonococcal isolates from patients with co-existing chlamydial infection compared with 57.9% (62/107) for those without chlamydial infection. Exact logistic regression analysis showed that the slightly increased sac-4 prevalence among chlamydia positive patients (p=0.2) virtually disappeared when serovar status was taken into account (p>0.9). Conclusion: The sac-4 gene of the gonococcus does not increase the risk for mixed chlamydial infection.